Paragon (ANZGOG-0903): Phase 2 Study of Anastrozole in Women With Estrogen or Progesterone Receptor–Positive Platinum-Resistant or -Refractory Recurrent Ovarian Cancer. Issue 5 (June 2017) - Bonaventura, Anthony; O'Connell, Rachel L.; Mapagu, Cristina; Beale, Philip J.; McNally, Orla M.; Mileshkin, Linda R.; Grant, Peter T.; Hadley, Alison M.; Goh, Jeffery C.H.; Sjoquist, Katrin M.; Martyn, Julie; DeFazio, Anna; et al.
Abstract : Background: There is some evidence that a subset of patients with recurrent ovarian cancer may benefit from antiestrogen therapy. The Paragon study is a basket protocol that includes a series of phase 2 trials investigating the activity of anastrozole in patients with estrogen or progesterone receptor–positive recurrent gynecological cancers. We report the results of treatment in patients with platinum-resistant or -refractory recurrent epithelial ovarian cancer. Methods: Postmenopausal women who had estrogen and/or progesterone receptor–positive platinum-resistant or platinum-refractory recurrent ovarian cancer and disease measurable by Response Evaluation Criteria In Solid Tumors (RECIST) version 1.1 or GCIG (Gynecologic Cancer InterGroup) CA-125 criteria were eligible. Patients received anastrozole 1 mg daily until progression or unacceptable toxicity. The study was prospectively registered (ACTRN12610000796088). Results: There were 49 evaluable patients, and clinical benefit was observed in 13 (27%; 95% confidence interval [CI], 16%–40%). There were no complete or partial RECIST version 1.1 responses. Clinical benefit was associated with higher global quality-of-life scores. Median progression-free survival was 2.7 months (95% CI, 2.0–2.8 months). The median duration of clinical benefit was 2.8 months (95% CI, 2.6–5.7 months). Most patients (83%) progressed within 6 months. Seven patients continued on treatment for longer than 6 months. Anastrozole was well tolerated in most patients. Subgroup analysis suggested greater clinical benefit in patients with tumors with estrogen-receptor histoscore of more than 200, but this difference was not statistically significant. Conclusions: A subset of patients with estrogen- or progesterone-positive platinum-resistant or platinum-refractory recurrent epithelial ovarian cancers derives clinical benefit from anastrozole, with acceptable toxicity. The challenge remains how to identify them.